2005
DOI: 10.1093/aje/kwi114
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoking and Colorectal Cancer: APC Mutations, hMLH1 Expression, and GSTM1 and GSTT1 Polymorphisms

Abstract: The contribution of cigarette smoking to sporadic colorectal cancer may differ according to molecular aspects of the tumor or according to glutathione S-transferase M1 (GSTM1) or glutathione S-transferase T1 (GSTT1) genotype. In the prospective Netherlands Cohort Study on Diet and Cancer, adjusted incidence rate ratios for 1986-1993 were computed for overall colorectal cancer, tumors with and without adenomatous polyposis coli (APC) mutations, and tumors with and without human mut-L homologue 1 (hMLH1) express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 29 publications
4
35
0
2
Order By: Relevance
“…99,100 Our finding of no interaction between GSTM1 genotype and smoking is consistent with the pooled analysis of Smits et al 64 and with other studies. [101][102][103][104][105] As in the present study, other studies do not suggest an interaction between GSTM1 genotype and meat intake. 98,103,106,107 Similar to the findings of Turner et al, 96 our data did not suggest an interaction between GSTM1 genotype and intake of green leafy vegetables.…”
Section: Discussionsupporting
confidence: 58%
“…99,100 Our finding of no interaction between GSTM1 genotype and smoking is consistent with the pooled analysis of Smits et al 64 and with other studies. [101][102][103][104][105] As in the present study, other studies do not suggest an interaction between GSTM1 genotype and meat intake. 98,103,106,107 Similar to the findings of Turner et al, 96 our data did not suggest an interaction between GSTM1 genotype and intake of green leafy vegetables.…”
Section: Discussionsupporting
confidence: 58%
“…Some (34,(49)(50)(51) but not all(52-54) prior studies have reported a lack of association between smoking and colorectal cancer. Other studies have examined cofactors such as subject's metabolic genotype in tobacco carcinogen metabolism (55,56) and tumour characteristics (55,57) and found smoking to be associated with subgroups defined by these cofactors.…”
Section: Discussionmentioning
confidence: 99%
“…In the questionnaire, tobacco smoking was addressed through questions on smoking status (never, former, or current smoker) and inhalation for cigarette, cigar, and pipe smokers (26,27).…”
Section: Exposure Assessmentmentioning
confidence: 99%